Холодное уплотнение микропорошков кубического нитрида бора без применения пластификаторов - Никишина, М.В.; Петруша, И.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
A compaction of the CBN classified flour without plasticizing agent by shaking down, tamping fill and compression using press mold has been investigated. The peculiarities of the time dependence shaking down compactness denotes a formation of the dynamic stable arched structure. The ascertained porosities of the structures are 57,8; 44,5; 42,1 and 40,1 % for КМ 5/3, 10/7, 20/14 and 40/28 powders, respectively. After the tamping fill compaction like the compression using a press mold the porosities decrease to 41,6–37,9 %. The findings are useful for a practice of the HP-HT experiments and CBN sintering technology.